SISTEM PAKAR DIAGNOSA PENYAKIT GANGGUAN TIDUR DENGAN METODE FORWARD CHAINING BERBASIS WEB (STUDI KASUS : UPTD PUSKESMAS TELAGA DEWA KOTA BENGKULU) - Ahmad Revaldo; Yupianti Yupianti; Ila Yati Beti (UNIVED Press, 2023)
Abstract—The necessities of life force people to work to fulfill their daily lives. In general, humans work during the day and rest at night. A lot of time spent working requires humans to rest to recover their physical condition. Sleep is an important phase in daily activities that is useful for balancing human life. Everyone's sleep needs are different. Many people are long-sleepers who need 9 to 10 hours of sleep a night while others are short-sleepers who only need less than 6 hours of sleep each night. Long sleep is not always associated with sleep disturbances. Besides that most people are not medically trained, therefore the authors intend to design an